On the Chebyshev Polynomial for a Certain Class of Analytic Univalent Functions - Shahram Najafzadeh; Mugur Acu (Journal of Function Spaces)
In this work, by considering the Chebyshev polynomial of the first and second kind, a new subclass of univalent functions is defined. We obtain the coefficient estimate, extreme points, and convolution preserving property. Also, we discuss the radii of starlikeness, convexity, and close-to-convexity.